A new historical perspective on the European construction: Charles-Irénée Castel de Saint Pierre, a naive idealist and/or a huge visionary - Oana IUCU (Diversitate si Identitate Culturala in Europa)
The European idea is the result of reflections of enlightened minds that have guided and shaped the evolution of deep thinking on this subject over the centuries. To believe that only in recent decades has such a topic been widely discussed in public would not only be unjust but also insufficient for the scientific documentation needed on this subject. The oscillation between idealism and visionary thinking of these enlightened minds, including Charles-Irénée Castel, abbé de Saint-Pierre, was the major challenge of their reflections. At the same time, without the substantial contributions of beautiful minds such as those of Voltaire, Rousseau (names we find in the present analysis), we believe that the current European construction would not have been possible. We deem their names, including that of Charles-Irénée Castel, Abbot of Saint-Pierre, should be included in the list of the ‘founding fathers’ of the Europe envisioned by intellectuals of the time, both visionaries and idealists.